Implementation Analysis Of Planning And Budgeting Policies In Achieving Performance Targets Of Regional Government Work Units (Skpd) In Cirebon Regency - Ramdhani, Harri; Syarif Hidayat, Ii; Setiadi, Ade; Sugiyarsih, Susi (LPPM STIA Lancang Kuning Dumai, 2026)
This research aims to analyze the implementation of planning and budgeting policies in achieving performance targets within Regional Government Work Units (Satuan Kerja Perangkat Daerah, SKPD) in Cirebon Regency. The study is grounded in the concept of performance-based budgeting and public sector management reform, emphasizing alignment between policy planning, resource allocation, and institutional performance accountability.The background of this research lies in the gap between planned performance targets and their realization, which indicates that the policy implementation of planning and budgeting has not been fully effective. This condition reflects the challenges faced by regional governments in integrating planning documents (RKPD, Renstra, and Renja) with the budgeting system (APBD) to support measurable and outcome-oriented performance. The research investigates the processes, actors, and institutional mechanisms that influence the effectiveness of planning and budgeting implementation.This study adopts a qualitative descriptive approach supported by quantitative indicators derived from official performance reports. Data were collected through interviews, document analysis, and field observation within several SKPDs in Cirebon Regency, including the Regional Planning, Research, and Development Agency (Bappelitbangda), the Regional Financial Agency (BKAD), and the Inspectorate. The analytical framework refers to Edward III’s policy implementation model, which identifies communication, resources, disposition, and bureaucratic structure as key variables influencing policy outcomes.The findings reveal that the implementation of planning and budgeting policies in Cirebon Regency has been carried out procedurally in accordance with applicable regulations but has not yet achieved optimal synchronization between program planning and budget realization. The most significant constraints include weak coordination among SKPDs, limited technical capacity in translating strategic plans into operational budgets, and inconsistent policy communication between decision-makers and implementers. Nevertheless, the commitment of leadership and gradual improvements in institutional capacity have contributed positively to enhancing policy implementation.This research concludes that successful planning and budgeting implementation requires not only regulatory compliance but also the strengthening of inter-agency coordination, human resource competencies, and leadership commitment. The study contributes to the development of local governance studies by providing empirical evidence of the interrelationship between planning, budgeting, and performance accountability within Indonesia’s decentralized government framework.